KONSEP GERAK PADA GAMBAR: Kajian Faktor-Faktor Pembentuk Unsur Visual Konsep Gerak Untuk Menarik Atensi Audiens - Dewi, Agustina Kusuma (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
At least the research related to the concept of motion in the image has made it difficult to determine the factors that in content construction can measure the level of reliability of its application. In order to identify factors that are related to the application of the Motion Concept in Pictures, the authors conducted several stages of pre-experimental research. Some data analyzed by the author are produced using pre-experimental studies with the development of questionnaire instruments using convenience sampling techniques. The results were tested for significance using Chi-Square and Single Factor analysis. However, related to the application of the Motion Concept in Pictures, there are a number of things that have not been considered, namely the use of Stimuli and Novelty Intensity factors as forming visual elements, consideration of the use of quasi-experimental research with more reliable sampling techniques, and consideration of cultural modalities in applying Motion Concepts on picture. Keywords: Motion Concept, Movement, Visual Vocabularies